2019
DOI: 10.1186/s12883-019-1386-3
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma D-dimer levels are associated with short-term poor outcome in patients with acute ischemic stroke: a prospective, observational study

Abstract: Background Elevated levels of plasma D-dimer increase the risk of ischemic stroke, stroke severity, and the progression of stroke status, but the association between plasma D-dimer level and functional outcome is unclear. The aim of this study is to investigate whether plasma D-dimer level is a determinant of short-term poor functional outcome in patients with acute ischemic stroke (AIS). Methods This prospective study included 877 Chinese patients with AIS admitted to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 48 publications
2
16
1
Order By: Relevance
“… 13 , 21 Yao et al conducted a prospective study enrolling 877 Chinese patients with ischemic stroke and also confirmed that higher D-dimer level was related to poor clinical outcome. 8 However, this prospective study only collected admission D-dimer and the predictive value was lower compared with that of D-dimer level at 48 h in our study (AUC, 0.66 vs 0.73). There were 2 hypotheses regarding to the relationship between D-dimer and functional outcomes of ischemic stroke.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“… 13 , 21 Yao et al conducted a prospective study enrolling 877 Chinese patients with ischemic stroke and also confirmed that higher D-dimer level was related to poor clinical outcome. 8 However, this prospective study only collected admission D-dimer and the predictive value was lower compared with that of D-dimer level at 48 h in our study (AUC, 0.66 vs 0.73). There were 2 hypotheses regarding to the relationship between D-dimer and functional outcomes of ischemic stroke.…”
Section: Discussioncontrasting
confidence: 56%
“… 10 In patients treated with IV tPA, coagulation parameters including fibrinogen 11 , 12 and D-dimer 13 were also reported to be related to the prognosis for ischemic stroke. However, as most studies 8 , 11 13 only investigated the clinical significance of one coagulation parameter at one or two time points, still much is unknown on variation trends of the coagulation parameters before and after IV tPA, and their association with prognosis of patients treated with IV tPA.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, they might reflect diffuse local thrombosis or, less likely, embolism. In this setting, high D-dimer values may reflect thrombus formation, but they can also act as acute-phase enhancer of the inflammatory cascade and stimulates monocyte synthesis and release of proinflammatory cytokines, which can contribute to the occurrence of stroke [6]. We cannot ascertain a specific correlation of the DWI findings with SARS-CoV2 infection in our patient.…”
Section: Discussionmentioning
confidence: 86%
“…Finally, 22 prospective cohort studies (3,8,9,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) were included into this meta-analysis. Zakai et al reported the correlations between D-dimer levels and the risks of stroke and hemorrhagic stroke (HS); therefore, it was analyzed as two studies separately (26,27).…”
Section: Resultsmentioning
confidence: 99%